Users evaluation of a Spanish eHealth pediatric website. (November 2021) - Nievas-Soriano, Bruno José; García-Duarte, Sonia; Fernández-Alonso, Ana María; Bonillo-Perales, Antonio; Parrón-Carreño, Tesifón
Highlights: Pediatric eHealth websites can help parents with their decisions making. There are few evaluations of these websites performed from the point of view of the users. A quantitative evaluation was performed using a validated questionnaire. eHealth pediatric websites can be perceived by the users as usable, useful, trustworthy and accesible. Some characteristics of the users are associated with a better perception of different aspects of these websites. Abstract: Background: Parents use the Internet to take decisions about their children's health, but few resources have focused on eHealth technology evaluations from their point of view. Objective: The main aim of this research was to evaluate a Spanish eHealth pediatric website for parents. Methods: A previously validated web questionnaire was used to evaluate five domains: usability, utility, trust and confidence, well-child section and accessibility of the website. Univariate, bivariate and multiple linear regression analyses were performed. Results: 516 users participated in the research and rated the website as usable, useful, trustworthy and accessible. Higher scores were given by the participants who relied most on the Internet for taking decisions about health; by the participants who used a smartphone to access the pediatric website; by the participants who knew the website the longest; and by the participants who had accessed it more times. No differences in the evaluations of the website were found regarding age, education level or household income of the participants. Conclusions: eHealth pediatric websites, written by a pediatrician in an easy to understand language, can be perceived as usable, trustworthy, useful and accessible by their users and consequently help them with their decisions making. Some characteristics of the users are associated with a better perception of these websites.